PRARANCANGAN PABRIK SODIUM TRIPOLYPHOSPHATE DARI ASAM FOSFAT DAN NATRIUM KARBONAT DENGAN KAPASITAS 70.000 TON/ TAHUN - , RIZKY BERLIANA WIJAYANTI; , Indra Perdana, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sodium tripolyphosphate (STPP) is legally used as additive which is widely used to improve foodâs quality, particularly for meat and fish products. This compound is also used in baking powder, cola, and detergent manufacturing. Food additives demand is expected to increase as the high growth in per capita consumption, along with population growth. Food additives demand will increase as food industries continue to develop. This plant is designed to produce STPP from phosphoric acid, sodium carbonate, and sodium hydroxide with a capacity of 70.000 tons/ year and purity of 94%. The production process runs continuously for 330 days in a year. Manufacturing process of STPP is carried out in three steps. First, phosphoric acid purification is obtained by reaction with ammonia to remove impurities at 90ËC and 1 atm. The second step is synthesis at which monoammonium phosphate produced from the first step reacts with sodium carbonate and produce sodium ammonium phosphate. The product reacts with sodium hydroxide to produce orthophosphate mixture. The next step is calcination to convert orthophosphate to STPP. The raw materials required are phosphoric acid as much as 11.523,2981 kg/hour